Finite-time passivity for neutral-type neural networks with time-varying delays – via auxiliary function-based integral inequalities - Saravanan, Shanmugam; Syed Ali, M.; Alsaedi, Ahmed; Ahmad, Bashir (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we investigated the problem of the finite-time boundedness and finitetime passivity for neural networks with time-varying delays. A triple, quadrable and five integral terms with the delay information are introduced in the new Lyapunov–Krasovskii functional (LKF). Based on the auxiliary integral inequality, Writinger integral inequality and Jensen’s inequality, several sufficient conditions are derived. Finally, numerical examples are provided to verify the effectiveness of the proposed criterion. There results are compared with the existing results.